Antibacterial activity of camel milk and whey in combination with some antibiotics against vancomycin resistant Staphylococcus aureus - Lubna Abdallah; Ikram Sawafta; Nenaro Zaid; Rahaf Dabe; Mervana Mohtaseb; Monya Tubelleh; Malak Khader (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The main goal of this research is to observe the antibacterial activity of camel milk and whey in combination with clindamycin, doxycycline, meropenem, trimethoprim sulfamethoxazole and vancomycin antibiotics against Vancomycin resistant Staphylococcus aureus (VRSA) and Staphylococcus aureus (ATCC 6538P). Micro-broth dilution method was used to measure the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for all antibiotics, milk and whey samples. For further antibacterial investigation, the fractional inhibitory concentration (FIC) was also determined. The interpretations of the activity of camel milk and whey combined with the five examined antibiotics produced remarkable synergistic activity in most combinations against both VRSA and S. aureus. It is noticeable that camel milk showed a synergistic effect with clindamycin, doxycycline and trimethoprim sulfamethoxazole against VRSA and S. aureus. Moreover, camel whey exhibited a synergistic effect with clindamycin and doxycycline against the two isolates. Based on the obtained results, it is concluded that there was an additive or indifferent effect rather than synergism when combining camel milk and whey with antibiotics that targeted bacterial cell wall synthesis. Otherwise, when combining camel milk and whey with antibiotics targeting protein synthesis or targeting folate synthesis a synergistic effect was observed. The present research clearly showed that camel milk is considered a promising natural product that plays an important role in elevating the susceptibility of bacteria to some antibiotics.